Sociodemographic Factors Associated with Video Game Addiction in Schoolchildren from the South-Central Region of Chile - Alejandra Rodríguez-Fernández; Marcela Ruíz-De la Fuente; Eduard Maury-Sintjago; Sofía Petersen; Valentina Paredes; Bárbara Montero (MDPI AG, 2024)
Video game addiction is a worldwide concern, particularly in schoolchildren where it has impact on academic, social, and emotional spheres. The objective of this study was to determine the sociodemographic factors associated with video game addiction in schoolchildren from the south-central region of Chile. Methods: An analytical cross-sectional study that included a sample of 308 schoolchildren was performed. Sociodemographic factors were analyzed and levels of video game addiction was assessed using the Video Game Addiction Test (VAT) developed by Chóliz and Marco. A general linear regression model (ANCOVA) (α = 0.05) was applied (STATA v16). The prevalence of video game use was 82.7%, while addiction reached 10%. Risk factors associated with the increased risk of addiction were as follows: being male (β = 13.99; p < 0.001); being in the care of another relative (β = 11.1; p < 0.001); a higher number of people in the household (β = 11.2; p < 0.001); the caregiver in employment (β = 12.8; p < 0.001); and not performing extracurricular physical activity (β = 9.9; p < 0.001).